EFFECTS OF A DISTANCE LEARNING COURSE FOR TEACHERS ON PROPORTIONALITY ON THEIR PERCEPTION OF SELF-EFFICACY - Laëtitia DRAGONE; Gaëtan TEMPERMAN; Bruno DE LIEVRE (Universitaria Publishing House, Craiova, 2024)
With the aim of strengthening the didactic capacity of teachers in the Frenchspeaking Belgium in the teaching of proportionality, we designed a distance training course. The training lasted four weeks and benefited a total of 93 teachers. To evaluate the effectiveness of this training, we administered a pre-test and a post-test, assessing respectively the teachers' self-efficacy, their feeling of confidence in the didactic field and their satisfaction with the training. The results showed a significant improvement in teachers' confidence and self-efficacy. These positive results underline the importance and relevance of offering further online training courses focusing on the teaching of proportionality, with the aim of optimizing teachers' pedagogical skills in this specific mathematical area.